The Tradition of Urdu-Hindi Language's Communication and Interaction - Niaz, Shabnam; Anjum, Naila (sourcecoder, 2023)
Urdu and Hindi languages are like two companions playing together in the same courtyard, constantly influencing and accepting each other's impact. Urdu, being a captivating and versatile language has beautifully embraced numerous words from Hindi, just like it has done with other languages. This influence has led to create the notion that Hindi and Urdu are the same languages. This article presents after the study of historical references, linguistic facts, and language rules to demonstrate that Urdu has accepted the influences of Hindi, just as it has accepted influences from other languages. However, despite this Urdu language has firmly maintained its identity, position, and status. Urdu and Hindi, in their respective places, are complete means of expressing the emotions and feelings of their speakers and in this regard, they have their own unique identities and status.